A High-Efficiency, Low-Cost Solution for On-Board Power Converters. (25th November 2012) - Boscaino, V.; Capponi, G.
Abstract : Wide-input, low-voltage, and high-current applications are addressed. A single-ended isolated topology which improves the power efficiency, reduces both switching and conduction losses, and heavily lowers the system cost is presented. During each switching cycle, the transformer core reset is provided. The traditional tradeoff between the maximum allowable duty-cycle and the reset voltage is avoided and the off-voltage of active switches is clamped to the input voltage. Therefore, the system cost is heavily reduced and the converter is well suited for wide-input applications. Zero-voltage switching is achieved for active switches, and the power efficiency is greatly improved. In the output mesh, an inductor is included making the converter suitable for high-current, low-voltage applications. Since the active clamp forward converter is the closest competitor of the proposed converter, a comparison is provided as well. In this paper, the steady-state and small-signal analysis of the proposed converter is presented. Design examples are provided for further applications. Simulation and experimental results are shown to validate the great advantages brought by the proposed topology.